Do Linguistic Style and Readability of Scientific Abstracts Affect their Virality? - Guerini, Marco; Pepe, Alberto; Lepri, Bruno (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Reactions to textual content posted in an online social net- work show different dynamics depending on the linguistic style and readability of the submitted content. Do similar dy- namics exist for responses to scientific articles? Our intuition, supported by previous research, suggests that the success of a scientific article depends on its content, rather than on its linguistic style. In this article, we examine a corpus of sci- entific abstracts and three forms of associated reactions: ar- ticle downloads, citations, and bookmarks. Through a class- based psycholinguistic analysis and readability indices tests, we show that certain stylistic and readability features of ab- stracts clearly concur in determining the success and viral ca- pability of a scientific article.